Drivers of sustainable natural capital, forest capital, and green growth in Sweden: Rise and fall scenario of material productivity - Andrew Adewale Alola; Seyi Saint Akadiri (Ecological Indicators, 2023)
Given Sweden’s impressive performance on green growth among the European Union countries, this study is focuses on examining the responses of green growth, sustainable natural capital, sustainable forest capital, and carbon footprint to environmental-related innovation and material productivity while employing population to control for unobserved forces. By employing the dataset that spans over 1970–2019 alongside using suitable econometric approaches, the short- and long-run relationships alongside the Granger causality evidence are provided. The revelation from the result shows that environmental-related innovation promotes sustainable natural capital (by elasticity of ∼ 0.04), promotes sustainable forest capital (by elasticity of ∼ 0.13), improves green growth (by elasticity of ∼ 0.01), but spur carbon footpint (by elasticity of ∼ 0.01) especially in the long-run. Importantly, the investigation further reveals that material productivity exhibits an inverted U-shaped relationship with sustainable natural capital, sustainable forest capital, and carbon emission, thus affirming the validity of material productivity Kuznets curve (MPKC) i.e., rise and fall scenario of material productivity. Meanwhile, while population produces desirable carbon emission and green growth outcomes, it hampers both sustainable natural capital and sustainable forest capital especially in the long run. Given these results, relevant and implementable policy guidelines are highlighted for policy makers and other stakeholders in Sweden.